Diminishing partnership home financing concept as an alternative to Bai Bithaman Ajil (BBA): empirical evidences from the perceptions of Shariah scholars and bankers - Abdul Razak, Dzuljastri; Md Taib, Fauziah (2009)

(untitled)
Meera and Abdul Razak (2005) suggested that the Diminishing Partnership (DP) Home Financing concept can be a viable alternative to Bai Bithaman Ajil (BBA) Home Financing. They argued that DP concept can address issues faced by BBA which is still the main financing mode of Islamic financial institutions to date. The major issues that have arisen are related to the concepts used, methods of computation, pricing based on interest rate benchmark, Shariah compliant, justice and societal well being. On the other hand, the DP concept is claimed to be free from the above mentioned shortcomings and said to be in line with the spirit of Islam, which promotes risk sharing and its pricing based on rental is considered to be just and fair. As these issues requires in depth understanding of the Shariah parameter as well and banking operations, semi-structured interviews were conducted with six Shariah scholars and six bankers to seek their opinions and viewpoints on the variables investigated. The Shariah scholars generally agreed that DP concept possess greater justice, equity and follows the true spirit of Islam. Contrary to expectation, the overall views of the bankers support the implementation of DP, although there were a few reservations regarding its operations. The actual implementation of DP is a challenge for bankers which require a paradigm shift from their present role as traditional financiers.